The impact of different demographic variables on determinants of university choice decision: A study on business administration students of the foundation - Tamtekin Aydın, O.; Bayır, F. (Edam, 2016)
By examining the relevant literature, many factors can be determined as effecting factors on university choice process. However, existing literature does not fully explore the effect of demographic variables on these factors. This research is aimed at identifying the relationship between university selection criteria and demographic variables, defined in the study as gender, family income level, types of high school graduated from, and whether working or not during the education period in the business administration departments of the foundation universities in Istanbul. The study was designed by descriptive research method using a survey. The face-to-face questionnaires were conducted to the students during the 2014-2015 academic year of selected foundation universities. Convenience sampling method was used to determine the participants of the study. A total of 600 questionnaire forms were delivered to the students in these universities, the 510 questionnaire forms were counted as valid. At the end of the study, based on the relevant literature, 13 determinants that play an influential role on students’ decisions were obtained. Next, the ranking of the university choice criteria on Turkish students’ decisions was proposed. Lastly, the relationships between demographic variables outlined above and determinants of the university choice process are then presented. © 2016 EDAM.
Keywords: Business Administration Departments; Demographic Variables; Determinants Of Students' University Choice Decision; Foundation Universities; Higher Education